Incorporation of synthetic macrofibres in Warm Mix Asphalt - Morea, Francisco (2018)
The reinforcement of asphalt concrete with fibres is not a common practice in the pavement field. Although some research papers refer to the use of microfibres, the behaviour of asphalt concrete incorporating macrofibres has not been studied. Warm Mix Asphalt (WMA) is environmentally friendly because it is possible to reduce emissions and fuel consumption. WMA technologies allow the reduction of mixing temperatures. The WMAs performances must be better than or similar to traditional Hot Mix Asphalts (HMAs). This work explores the benefits of incorporating synthetic macrofibres in WMA. Important improvements in rutting performance were observed when comparing to WMA without fibres, outperforming even HMA. Improvements in fracture behaviour at low to medium temperatures represent another benefit of macrofibre incorporation, confirming the advantages of the synergic combination of WMA and synthetic macrofibres.